Burkina Faso, géoressource et société : un projet scientifique Sud-Nord au service d’une gestion raisonnée des géoressources en Afrique intertropicale - Vincent Bouchot; Emile Bangraogo Kaboré; Yann Itard; Nathalie Courtois; Sylvain Somé; Aïssata Tapsoba Sy; Gilles Récoché (VertigO)
In tropical Africa, the first hundred meters below the surface are the site of intense lateritic weathering process. By transforming the rock, this alteration substantially facilitates access to many georesources (e.g. gold, clay, groundwater) by national operators. Consequently, the methodological development of regolith map and of derived maps predicting location of gold resource and groundwater is a prerequisite for rational management of georesources. This methodology was developed between 2007 and 2008, under the scientific project "Burkina Faso, Georesources and Society, » by the Geological Survey of Burkina Faso (BUMIGEB) and France (BRGM), following a participatory South-North approach. To meet the expectations of end users (craftsmen, small businesses, regional planners, regional planners...), creating an end-user committee (COMUT) formalized the framework for needs expression and has played the role of committee steering to follow scientific activities throughout the project. Ultimately, this project allowed geological survey to master mapping methodology for the rational management georesources and in the future, to apply them to Burkina Faso or in other African areas affected by lateritic weathering. The South-North scientific collaboration has resulted in strengthening relations between the two geological surveys through the exchange of experiences, skills transfer and joint acquisition of know-how.